Pengaruh Pelvic Rocking Menggunakan Birthing Ball Terhadap Nyeri Punggung Ibu Hamil Trimester 3 Di BPM Nurul Fajriah Fahmawati A.MD.Keb - Nurul Fajriah Fatmawati; Tut Rayani Aksohini Wijayanti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
During pregnancy, a woman's body undergoes various changes that are categorized into three stages: the first trimester (weeks 0 to 14), the second trimester (weeks 14 to 28), and the third trimester (weeks 28 to labor). The third trimester is often marked by increased physical discomfort, including back pain caused by hormonal changes and growing pressure from the uterus on the lower body structures. One non-pharmacological approach to reduce this complaint is pelvic rocking exercise using a birthing ball. This method is a relaxation technique aimed at relieving pain, improving posture, and helping the body prepare for labor. This study employed a pre-experimental design with a One Group Pre-Test and Post-Test model, comparing participants’ conditions before and after the intervention. The sampling technique used was total sampling, involving 40 third-trimester pregnant women experiencing back pain at PMB Nurul Fajriah Fatmawati during the period of April to May 2025. Data were analyzed using the Wilcoxon test. The test results showed a significance value of p = 0.000, which is less than α = 0.05, indicating a statistically significant effect. Therefore, it can be concluded that pelvic rocking using a birthing ball is effective in reducing the intensity of back pain in third-trimester pregnant women.